A study of lipid profile and glycemic status in patients with chronic kidney disease of unknown etiology in Sri Lanka - Basnayake, Duminda B.; Sandamali, W. G. H.; Nayanamali, Ayesha; Wazil, Abdul W. M.; Siriwardena, R. M. P. A.; Thennakoon, T. M. C. I.; Dharmasiri, Thilak; Nanayakkara, Nishantha (International Journal of Research in Medical Sciences, 2020)
Background: Dyslipidemia and impaired glucose tolerance are common complications of chronic kidney disease (CKD) and are responsible for increased cardiovascular risk. Studies on lipid profile and glycemic status in CKD of unknown origin (CKDu) are scarce. The objective of this study was to evaluate the lipid profile and glycemic status of the patients with CKDu and to aid in preventing morbidity and mortality. Methods: The descriptive, cross sectional study was conducted in a rural CKDu endemic area, Girandurukotte. Data was collected from February 2018 to June 2019. For the diagnosis of CKDu, history and clinical features with supportive biochemical, renal biopsy and radiological evidence were taken as criteria. Blood samples were taken for serum creatinine, lipid profile and HbA1C. Already diagnosed patients with diabetes mellitus and dyslipidemia were excluded. Results: A total of 168 patients within the age range of 32-66 years (mean 50.3±7.7) were participated. There were 106 males (63%) 46.4% were farmers. Majority of the patients (65.5%) had normal body mass index (BMI) (mean 22.9 kg/m2, normal range 18.5-23.5%) followed by overweight (23.5-30 kg/m2) in 55 (32.7%) patients. The prevalence of dyslipidemia in CKDu was found to be 55.9%. Majority of the abnormality was seen in the HDL group with 68 (40.5%) patients having low HDL cholesterol (mean 44.7 mg/dl, SD=12.3). There was a significant rise in the serum triglyceride concentration (>150 mg/dl) in 53 (31.5%) (mean 152.4 mg/dl, SD=73.5) and total cholesterol (>200 mg/dl) in 30 (18%) patients (mean 182 mg/dl, SD=36.9). LDL cholesterol abnormality (>130 mg/dl) was seen in only 9 patients (mean 88.7 7658mg/dl, SD=25.4). From the total, 144 (85.7%) patients had abnormal HbA1C levels; 27 (16.1%) patients had HbA1C levels between 5.7% and 6.4% (pre-diabetes), and 117 (69.6%) patients had HbA1C level more than 6.5% (diabetes mellitus). There was no statistically significant association between HbA1C levels and BMI (p=0.29) or HbA1C and lipid abnormalities (p=0.32) Conclusions: The high prevalence of dyslipidemia, pre-diabetes and diabetes mellitus in patients with CKDu may accelerate the progression of chronic kidney disease and increase the risk of cardiovascular disease. Early detection, initiation of appropriate medication and early referral to the expertise will ameliorate morbidity and mortality.